2008
DOI: 10.2474/trol.3.76
|View full text |Cite
|
Sign up to set email alerts
|

Study of Belt Friction in Over-Wrapped Condition

Abstract: The property of belt friction in an over-wrapped condition was studied. A fractional expression with respect to the ratio of belt tensions was derived by this study. The Euler's belt formula was included as a special case in the equation derived. The equation is a function of the contact angle θ and two kinds of the coefficient of friction µ and µ b , where θ is wrapping angle of a belt around a cylinder, µ is the coefficient of friction between the belt and the cylinder and µ b is the coefficient of friction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 0 publications
1
9
0
Order By: Relevance
“…So far, the properties of belt friction in two and three times wrapping condition have been studied theoretically [1,2]. According to the results of these studies, it was found that a belt has self-locking property.…”
Section: Introductionmentioning
confidence: 99%
“…So far, the properties of belt friction in two and three times wrapping condition have been studied theoretically [1,2]. According to the results of these studies, it was found that a belt has self-locking property.…”
Section: Introductionmentioning
confidence: 99%
“…The belt tensions 1 1 2 , ", ′ T T T and 2 T ′ in Eq. (17) should be expressed by the function of T 4 .…”
Section: Theorymentioning
confidence: 99%
“…But so far, self-locking phenomenon of belt friction was not clearly understood. Imado clarified the mechanism of self-locking of belt in two times wrapping condition [2]. But as the theory was limited to the two times wrapping condition, somewhat severe condition was required to generate the self-locking.…”
Section: Introductionmentioning
confidence: 99%
“…Imado found the self-locking property of the belt in the course of his study and showed the theoretical self-locking condition for two and three times wrapping condition of belt (Imado, 2008;Imado, et al, 2013a). He devised a one-way clutch by utilizing the self-locking property of belt (Imado, et al, 2010;Imado, et al, 2013b).…”
Section: Introductionmentioning
confidence: 99%